Kajian reka bentuk troli di lapangan terbang antarabangsa Kuching - Siti Yusni bt, Azmi (Universiti Malaysia Sarawak (UNIMAS), 2007)
This research is about the using trolley at the KIA. By designing the new trolley, it will help to solve the user problem. This research is focus on the corporate identity, functions of the trolley and also the design of the trolley.